Agates from Mesoproterozoic Volcanics (Pasha–Ladoga Basin, NW Russia): Characteristics and Proposed Origin - Evgeniya N. Svetova; Sergei A. Svetov (Minerals, 2022)
Agate gemstones occurring in the Mesoproterozoic volcanic rocks of the Priozersk Formation (PrF) within the Pasha–Ladoga Basin (Fennoscandian Shield, NW Russia) were investigated to characterize the mineral and geochemical composition of the agates and provide new information concerning their origin. Optical and scanning electron microscopy, EDS microanalysis, X-ray powder diffraction, X-ray fluorescence spectrometry, Raman spectroscopy, inductively coupled plasma mass spectrometry (ICP-MS), and C-O isotope analysis were used for the study. Agate mineralization appears mostly as an infill of fissures, cavities, gas vesicles in massive and vesicular basalts, lava-breccias. The mineral composition of agates is dominated by alpha-quartz (fibrous chalcedony, microcrystalline and macrocrystalline quartz), but it also displays abundances of calcite. The characteristic red-brownish agate’s coloration is caused by multiple hematite inclusions distributed in an agate matrix. The study revealed the two phases of agate formation in the PrF volcanics, which are most likely controlled by two distinctly different fluids and/or their mixture. At first, agates appeared due to post-magmatic iron-rich fluids. The late hydrothermal activity was probably triggered by intrusion of gabbro-dolerite sill and resulted in the second phase of agate formation. We suggest that the late hydrothermal fluids remobilized the iron compounds from the crust of weathering underlying the PrF volcanics, which led to additional formation of vein agates and filling of gas vesicles with hematite-rich calcite/silica matter.